Young Central Americans: A Reading from the Written Media - Bryan Roberto Vargas Vargas (2019)
This study aims to describe the social spaces, social roles andtopics in which young Central Americans are mentioned in written mass mediapress between the years 2013 and 2017. Furthermore, this research belongsto youth studies that relate social conditions with the practices of those whoare in that period of life. The retrospectively analyzed data derives from a 612Central American news compilation from 2017 to 2013 of each online media’splatforms selected. The two main topics in which young people are mentionedare theoretically and historically discussed in depth, namely violence andeducation.